To mother - Nurshafitri Ya'akob (2019)
To Mother hopes to expound on the different expectations of the parent-child relationship that may not necessarily coincide with reality. It hopes to delve into the grief and loneliness one encounters when their preconceived perception of any of these two labels clashed.